Psychological beneficence as part of the principle of beneficence in non-reconstructive aesthetic surgeries - Garcia-Sánchez, Emilio (Medicina e Morale, 2023)
The beneficence of the patient in non-reconstructive aesthetic surgeries must always include not only the physical well-being, but the psychological well-being of the patient as well. This issue has been proven to be effectively targeted with the use of psychological consulting in those cases where the medical team ascertains the existence of psychological alterations. In said cases, for the beneficence and best interest of the patient, the ethical and medical choice is not to undergo the surgical procedure. Applying the Principle of Beneficence in aesthetic patients with stringency demands the use of psychological treatment to target the cause of the corporal discomfort or unsatisfaction. If the wrong can be treated it must always be eliminated as the seed that causes the damage, the complex or discontent and not merely attain the effects through surgery. There has been an increase of cases where the root of the problem is not of physical nature but psychological. In these cases, the use of a scalpel would not achieve beneficence.